Illegal Firearms Distribution In Support Of Papuan Separatist Movement - Muji Hartono*; Aloisius Mado; Asep Kususunanto (Riwayat: Educational Journal of History and Humanities, 2024)
The circulation of illegal firearms in Papua is the main driving factor in prolonging the separatist conflict in the region. These firearms are used by separatist groups to carry out acts of violence against security forces, civilians and public infrastructure. This resulted in loss of life and material, as well as hampering development and stability efforts in Papua. This journal discusses the sources and routes of distribution of illegal firearms in Papua, the impacts they cause, and the government's efforts to overcome them. Analysis shows that the circulation of illegal firearms originates from international smuggling networks, theft from security forces, and the manufacture of traditional firearms. The impacts include violence and human rights violations, disruption of security and stability, as well as obstacles to development and community welfare. The government's efforts to address the circulation of illegal firearms in Papua include law enforcement operations, cooperation with neighboring countries, and economic and social development programs. Comprehensive and sustainable efforts are needed from the government and various related parties to eradicate the circulation of illegal firearms and build peace in Papua.